الحوادث الارهابية في جمهورية مالي بين عامي 2015 و 2020م - Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي (Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي, 2023)
The contents of this article came in the form of facts and a chronological sequence of the spread of terrorism in Mali and its repercussions. In addition to the author's reliance on the most prominent news sites that document the situation, some testimonies and a number of media materials and press interviews, and accounts familiar with the matter on social networking sites. | جائت محتويات هذه المادة في صورة وقائع و تسلسل كرونولوجي لانتشار الارهاب في مالي و تداعياته. اضافة الى اعتماد المعد على ابرز المواقع الاخبارية التي توثق الاوضاع, و بعض الافادات و عدد من المواد الاعلامية و الحوارات الصحافية, و الحسابات المطلعة على الشأن في مواقع التواصل الاجتماعية.